INTRAPOPULATION GENETIC DIVERSITY ASSESSED IN TEPHROSIA CALOPHYLLA BEDD., A RARE MEDICINAL PLANT USING RAPD MARKERS - SASIKALA.T.P; VENKATESWARA RAO. S.; KAMAKSHAMMA,J. (International Journal of Pharma and Bio Sciences, 2013)
Tephrosia calophylla is a perennial under-shrub with a tuberous root and is known for its various therapeutic properties. Genetic diversity was analysed using RAPD primers among 10 accessions collected from the population of Talakona, Andhra Pradesh, India. Twenty random primers ,each with 10 bases generated a total of 47 polymorphic bands out of 70 total bands ,that showed 67.6% polymorphism . Genetic distance between each accession was calculated and dendrogram was constructed on the basis of the similarity matrix data by unweighed pair group method with average (UPGMA) cluster analysis. The analysis with RAPD markers reflected high level of diversity within the population in this species.